Use of solid extraction chromatography for determination of uranium in sea water and brine. Issue 55 (25th November 2016) - Prabhu, S.P.; Prasad, T.L.; Rao, D.D.
Abstract: Bench scale field trials were initiated for the development of effective technology for recovery of uranium from sea water using acrylonitrile absorbents synthesized by radiation grafting. One of the important needs is to ensure quality assurance for the accurate measurement of heavy metal ion concentrations from lean solutions such as sea water and brine. Efforts have been made at Bioassay Laboratory of Radiation Safety Systems Division in India to improve the radiochemical separation and detection techniques for rapid, sensitive and accurate estimation of uranium in sea water samples. The earlier method using ion exchange had disadvantages of being lengthy and required use of sulphuric acid. Hence, a method was developed for estimation of uranium concentration in natural sea water and brine (desalination plant effluents) samples by solid extraction chromatography (SEC) using UTEVA resin (Uranium and TEtraValents Actinides). This resin consists of dipentyl pentylphosphonate sorbed onto an inert polymeric support. Using SEC technique, the complete analysis results are available within a day and as the resin is very specific for uranium extraction from the samples, it is easier to eliminate interfering transition ions like vanadium and iron from the samples. This paper reports the standardization of radiochemical procedure for uranium from sea water and brine samples and its determination by alpha spectrometry.